2017
DOI: 10.2903/j.efsa.2017.4927
|View full text |Cite
|
Sign up to set email alerts
|

Pest categorisation of Spodoptera frugiperda

Abstract: The European Commission requested EFSA to conduct a pest categorisation of Spodoptera frugiperda (Lepidoptera: Noctuidae) a pest with hosts in 27 plant families. Favoured hosts include maize, rice and sorghum (Poaceae). Hosts also include crops within the Brassicaceae, Cucurbitaceae, Solanaceae, Rutaceae and other families. S. frugiperda is a taxonomic entity with reliable methods for identification. It is regulated in the EU as a harmful organism whose introduction into the EU is banned. It is native to tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 52 publications
0
44
0
1
Order By: Relevance
“…If the species can survive year-round in North Africa, then seasonal migrations into Europe could also occur. This would pose a severe threat to agriculture in Europe, and the fall armyworm is classed as a Quarantine Pest for the EU 17 . Further afield, the fall armyworm’s wide distribution in the Americas and Africa suggest that it could establish easily in East and Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…If the species can survive year-round in North Africa, then seasonal migrations into Europe could also occur. This would pose a severe threat to agriculture in Europe, and the fall armyworm is classed as a Quarantine Pest for the EU 17 . Further afield, the fall armyworm’s wide distribution in the Americas and Africa suggest that it could establish easily in East and Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license It is made available under a was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. (Goergen et al 2016;Jeger et al 2017). …”
mentioning
confidence: 99%
“…The FAW has no winter diapause (Sparks 1979) and its wintering range is constrained to warmer regions such as southern Florida and southern Texas in the United States . In 2016 it became invasive on the African continent where massive crop damages have been observed across sub-Saharan Africa in less than a year (Goergen et al 2016;Jeger et al 2017). …”
mentioning
confidence: 99%
“…Although S. eridania has been reported from California (Capinera, 2011; Capinera, 2014 cited in CDFA, 2016), the California Department of Food and Agriculture states that it has never been found in the environment of California but intercepted four times on bell peppers, cilantro, tree fern, and Asparagus sperengeri from Florida (CDFA, 2016). (Casmuz et al, 2010;EFSA PLH Panel, 2017), such a preference for any plant family is not found in S. eridiana (Montezano et al, 2014). The same authors report the occurrence of this species in crops of regional importance, which highlights the versatility and ability of this species to rapidly adapt in various regions of the Americas,…”
Section: 2mentioning
confidence: 88%
“…(), S. eridania has been found on at least 202 natural host plants in 58 botanical families, including both cultivated and non‐crop plants that could be considered as weeds (Appendix A). Compared to its close relative S. frugiperda Walker, for which 186 host plants have been cited with a clear preference for Poaceae (66 species) (Casmuz et al., ; EFSA PLH Panel, ), such a preference for any plant family is not found in S. eridiana (Montezano et al., ). The same authors report the occurrence of this species in crops of regional importance, which highlights the versatility and ability of this species to rapidly adapt in various regions of the Americas, feeding on cultivated plants including alfalfa, bean, beet, cabbage, cassava, cotton, maize, potato, soybean, sweet potato, and tomato, but also exploiting weeds as alternative hosts used by females for oviposition and by larger larvae when migrating.…”
Section: Pest Categorisationmentioning
confidence: 99%